Rekonfigurasi 33 Kanal Irigasi Menggunakan Modified Firefly Algorithm (MFA) - Markhaban Siswanto; Saiful Arfaah; Rukslin Rukslin; Muhlasin Muhlasin; Machrus Ali (Jurnal FORTECH, 2023)
Providing irrigation water on agricultural land aims to meet plants' water needs. In its use, irrigation water must be used optimally. An automatic irrigation system is needed to provide water to plants in the desired conditions. The irrigation canal system is a simulation system using a software program Matlab 2013b. Reconfiguration simulations applied to irrigation systems are used to increase efficiency and determine the amount of irrigation water to regulate the provision of irrigation water according to needs. As a controller comparison, an artificial intelligence method is used for controller tuning based on the Modified Firefly Algorithm (MFA). The furthest water discharge results can be reduced in the reconfiguration model with a minimum discharge before reconfiguration of 0.91308 pu, and after reconfiguration, it becomes 0.93337 pu. So by reconfiguring the network with MFA, you can reduce water discharge losses by 30.3337% from previous losses